The Role of Tumbler Products In Supporting Sustainable Consumption and Production in Generation Z - Dinda Suchi Wulandari; Usep Suhud (Economic, Management, Business and Accountancy International Journal, 2025)
The purpose of this study is to investigate how using tumblers might promote sustainable production and consumption, especially among Generation Z. By examining pertinent studies on green marketing, the Theory of Planned Behaviour, and sustainable consumption, the study takes a conceptual approach. According to the research, tumblers have changed from being basic drinking vessels to representing young people's ecologically sensitive way of life. Purchase intention and tumbler uptake are greatly impacted by a few important influencing variables, including as accessibility, social influence, favorable environmental views, and green marketing strategies. Using tumblers not only helps reduce plastic waste but also supports Sustainable Development Goal (SDG) 12 by reinforcing youth's social identity as change agents. According to the study's findings, tumblers are a major factor in changing consumer habits and are a long-term solution to reduce dependency on single-use plastics.